Regional Integration and Development - Schiff, Maurice (Washington, DC: World Bank and Oxford University Press, 2013)
The growth of regional trading blocks is now a major feature of international relations. This book examines regionalism from the viewpoint of developing countries, and provides a comprehensive account of existing economic theory, and empirical results. In a thorough analysis of the politics, and dynamics of regionalism, the book considers the relationship between regionalism, and multilateralism, and explores the economic advantages of non-discriminatory trade liberalization, which the authors argue should be exploited to the maximum extent. Designed as a practical guide for policymakers whose countries are considering membership in a trade block, this book will also be of interest to scholars, and students of international trade.